Characteristics of central cortex and upper-limb flexors synchrony oxygenation during grasping in people with stroke: a controlled trial study protocol - Zhao, Jiang-Li; Chen, Pei-Ming; Zhang, Tao; Xie, Hao; Xiao, Wen-Wu; Ng, Shamay S. M; Wang, Chu-Huai (Frontiers in Human Neuroscience, 2024)
Background: Upper limb motor impairment is a common consequence of stroke, and the effectiveness and underlying mechanisms of rehabilitation therapy for improving upper limb function remain uncertain. Functional near-infrared spectroscopy, a reliable wearable neuroimaging technique, holds promise for investigating brain activity during functional tasks. This study aims to explore the synchronous oxygenation characteristics of the central cortex and upper-limb flexors during a grasping task and investigate the rehabilitation mechanisms of upper limb motor function in individuals with stroke.Methods: Participants with stroke who demonstrate the ability to grasp and lift cubic wood blocks of different sizes (2.5cm 3 , 5cm 3 , and 10cm 3 ) using their affected hand will be divided into three groups: A, B, and C. Each group will consist of twenty stroke patients, resulting in a total of sixty participants with stroke. Additionally, twenty matched healthy subjects will be enrolled as a control group. Comprehensive assessments will be conducted before and after the intervention, including blood oxygen parameter monitoring of the cerebral cortex and upper limb flexors using fNIRS during the grasping task. Other assessments will include MyotonPRO, the Modified Ashworth Scale, the upper extremity section of the Fugl-Meyer Assessment, the Action Research Arm Test, and the Modified Barthel Index. The study will be undertaken between January 2024 and September 2025.The results of this trial will provide an in-depth understanding of the Characteristics of central cortex and upper-limb flexors synchronous oxygenation during grasping task and how it may relate to the rehabilitation mechanism of upper limb motor function in people with stroke.